Pengembangan Media Pembelajaran Bahasa Inggris untuk Siswa Sekolah Dasar dengan Berbantuan Teknologi Augmented Reality Berbasis Android - Fairus Suryani Munir (BADAN PENERBIT STIEPARI PRESS, 2023)
Textbook-based English learning media are still widely used in the learning process so as to make the learning atmosphere less attractive for students. The purpose of this study is to determine the results of testing, validity and practicality. The method used is the RnD using (MDLC) model. The instruments used are AR Product Testing Test Observation Sheet, Validity and Practicality Questionnaire Sheet. The results showed that at the blackbox testing stage, 23 markers can display 3D objects and sound well and clearly, markers can be displayed up to a height of 1 meter with a slope of 0°-60°, but at height of 1.25 meters with a slope of 0°-30 °, the specifications of the installed mobile device are a minimum of Android 7 OS and can function properly the minimum RAM required is 2GB, the average validity of augmented reality as an English learning media for elementary school students Android-based from material experts is 90 with a very valid category and media experts of 85 with a very valid category, and the practicality is at an average score of 88 with a very practical category and shows a positive response from students.